Crude protein requirements of light-weight feedlot steersduring a 35-d receiving period - SALINAS-CHAVIRA, J; LATACK, B C; PLASCENCIA, A; ZINN, D R A (The Indian Journal of Animal Sciences, 2023)
The influence of dietary crude protein (CP) levels on growth performance, morbidity, and estimated dietary net energy (NE) of light-weight crossbreed feedlot calves during a 35-d receiving period was evaluated. For the above, 108 crossbred steers (196±13 kg) were used in 35-d receiving trial. Steers were randomly allocated to 18 pens (6 steers/pen, 6 replicas/treatment). Treatments consisted of a steam flaked corn-based receiving diet (72:28 concentrate to forage ratio) containing 12.5, 13.5 and 14.5% CP. Crude protein level in diet was manipulated by replacing steam flaked corn by canola meal. Steers were allowed ad lib. access to their experimental diets. Morbidity averaged 32%, and was not affected by treatments. Increasing the level of dietary CP improved average daily weight gain, gain efficiency and tended to increase the ratio of observed-to expected dietary NE. Furthermore, in CP range from 12.5 to 13.5%, these effects were evident, but were not apparent at 13.5 to 14.5% CP. It can be concluded that high-energy receiving diet formulations containing 13.5 to 14.5% CP will optimise initial growth performance of light-weight (~200 kg BW) feedlot calves. However, present effect may be more a function of achieving metabolisable amino acid rather than metabolisable protein requirements.